Acceptance of Biometric Payment Security Technology among Romanian Consumers - Gârdan, Daniel Adrian; State, Olimpia; Gardan, Iuliana Petronela; Baicu, Claudia Gabriela; Hristea, Anca Maria; Moise, Daniel (Transformations In Business & Economics, 2024)
More than ever the need to assure the security of online channels and the interface between online and offline transactions is very present and very important for business customers and individuals alike. Our paper investigates the validity of a model comprising variables specific to TAM (technology acceptance model) and UTAUT (Unified Theory of Acceptance, and Use of Technology) that explains the complex relationship between factors that can influence the adoption of biometric security technology with direct application in the financial services and payments field. The research made on a final validated sample of 1057 individuals filtered to be active users of biometric security devices and applications shows that performance expectancy along with facilitating conditions and social influence have a pretty well-defined effect on the perceived utility of the biometric technology, effect translated with the help of trust and intention to use towards usage behaviour.